What can we learn from the historic road safety performance of high-income countries?. Issue 1 (2nd January 2020) - Bhalla, Kavi; Mohan, Dinesh; O'Neill, Brian
Abstract: Road traffic deaths in high-income countries (HICs) have been steadily declining for five decades, but are rising or stable in low- and middle-income countries (LMICs). We use time-series cross-sectional methods to assess how age- and sex- specific death rates evolved in 20 HICs during 1955–2015, controlling for income, population density and urbanization. Past work has attributed improvements in safety in HICs to income growth, suggesting that countries intervene when they become richer (Kuznets hypothesis). In contrast, we show that HICs had statistically significant declines in road traffic injuries starting in the late 1960s that persist after controlling for income effects, and inclusion of a lagged dependent variable. These findings are consistent for all age-sex groups but the effects are strongest for the elderly and young children. We argue that the reversal in the traffic injury trend did not occur because HICs reached an income threshold. Instead, the 1960s were a period of paradigmatic change in thinking about road safety. Subsequent, safety improvements occurred because countries at different income levels established regulatory institutions that had a legislative mandate and financial resources to conduct large-scale safety interventions.